Oriented responses of grapevine moth larvae Lobesia botrana to volatiles from host plants and an artificial diet on a locomotion compensator - Becher, P. G.; Guerin, Patrick (My University, 2009)
Larvae of the grapevine moth Lobesia botrana (Lepidoptera: Tortricidae) are a major pest of vine, Vitis vinifera. As larvae have limited energy reserves and are in danger of desiccation and predation an efficient response to plant volatiles that would guide them to food and shelter could be expected. The responses of starved 2nd or 3rd instar larvae to volatile emissions from their artificial diet and to single host plant volatiles were recorded on a locomotion compensator. Test products were added to an air stream passing over the 30 cm diameter servosphere. The larvae showed non-directed walks of low rectitude in the air stream alone but changed to goal-oriented upwind displacement characterised by relatively straight tracks when the odour of the artificial diet and vapours of methyl salicylate, 1-hexanol, (Z)-3-hexen-1-ol, terpinen-4-ol, 1-octen-3-ol, (E)-4,8-dimethyl-1,3,7-nonatriene and (Z)-3-hexenyl acetate were added to the air stream. This chemoanemotactic targeted displacement illustrates appetence for certain volatile cues from food by starved Lobesia larvae. Analysis of the larval behaviour indicates dose dependent responses to some of the host plant volatiles tested with a response to methyl salicylate already visible at 1 ng, the lowest source dose tested. These behavioural responses show that Lobesia larvae can efficiently locate mixtures of volatile products released by food sources as well as single volatile constituents of their host plants. Such goal-oriented responses with shorter travel time and reduced energy loss are probably of importance for larval survival as it decreases the time they are exposed to biotic and abiotic hazards. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: grapevine moth; servosphere; olfaction; chemoanemotaxis; behaviour; behavioral-responses; rhodnius-prolixus; drosophila larvae; nonhost plant; codling moth; wind-tunnel; attraction; females; odor; identification